CHALLENGES AND MEASURES FOR ADMINISTRATIVE SECURITY AT THE LOCAL LEVEL DURING THE INTRODUCTION OF THE EUROPEAN CURRENCY UNIT (EURO) IN BULGARIA: CHALLENGES AND MEASURES FOR ADMINISTRATIVE SECURITY AT THE LOCAL LEVEL DURING THE INTRODUCTION OF THE EUROPEAN CURRENCY UNIT (EURO) IN BULGARIA - Simeonova, Iliana (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2025)
The topic of administrative security at the local level during the introduction of the euro in Bulgaria examines the main challenges and measures that local authorities need to undertake for the successful integration of the new currency in the country. With the transition to the euro, Bulgaria will need to ensure not only technical and logistical readiness but also efficient administrative processes that guarantee the security of the financial system. In this context, potential risks such as inflation, uncontrolled price increases, and public dissatisfaction, as well as social barriers related to the population's adaptation to the new currency, are analyzed. Undertaking serious measures for training public employees, adapting information technologies, and ensuring transparency in financial operations will be crucial to overcoming these challenges. Additionally, it is important for local authorities to coordinate their actions with the private sector and financial institutions to ensure a smooth transition to the euro. The strategies and practices implemented at the local level will determine the success of the overall process and strengthen the country's economic stability in the long term.